Design and modeling of a CMOS MEMS gravimetric sensor - Abdalrahman, M.G. (2014)
Design and modeling of a CMOS MEMS device using 0.35 Ã¬m CMOS technology is used to achieve high sensitivity on mass sensing is presented in this paper. The purpose of this paper is to investigate the effect of increasing beams lengths which support the membrane of the device, on the resonance frequency to achieve high sensitivity. A study on the effect of added mass on the device on natural frequency is also conducted. Mass sensitivity of this device is found to be 153 mHz/ng. At damping ratio of 0.0002, the resonant frequency of the resonator is 19.04 kHz with quality factor 3500. Â© (2014) Trans Tech Publications, Switzerland.